STUDENTS’ PERCEPTIONS OF CONTENT AND LANGUAGE INTEGRATED LEARNING AT SELECTED TECHNICAL UNIVERSITIES IN POLAND - Droździał-Szelest, Krystyna; Szczuka-Dorna, Liliana (Neofilolog, 2020)
The present article is an attempt to present the situation in the area of Content and Language Integrated Learning at some technical universities in Poland. It starts with a brief outline of CLIL methodology as well as its status in the context of Polish tertiary education, and then moves on to a discussion of the results of the study conducted among Polish and international students attending English-medium courses in their specialist areas, such as, for instance, engineering. The courses involve learning of new, difficult concepts as well as specialized vocabulary. The study took place in three universities which have been offering content instruction in English for a number of years. Its aim was to investigate problems and difficulties that students come across during the course of their studies in a foreign language, as well as their expectations concerning such a mode of education.